ICILS 2023: Digital kompetanse og algoritmisk tenkning hos norske niendeklassinger - Rohatgi, Anubha; Hatlevik, Ove E; Gudmundsdottir, Greta B; Erstad, Ola A; Björnsson, Julius K (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2024)
ICILS, the International Computer and Information Literacy Study, examines fourteen-year-olds’ digital competence and algorithmic thinking. The purpose of the study is to survey how well young people are prepared for academic, working and everyday life in a digital world. The study also enables comparison of results between different countries, reveals how the development of digital competence changes over time, and provides important insight into the effects of digitization on schooling. The ICILS survey has been conducted every five years since 2013. Norway participated in both 2013 and 2023, and thus we now have the opportunity to look at the development of digital competence over time. Denmark, Finland and Sweden also participated in the third round, which provides a unique opportunity to compare results and identify similarities and differences between these countries. This report presents the first findings for the third implementation of ICILS from a Norwegian perspective and provides a simple description of the main results. The report is aimed at a broad audience, especially school leaders, teachers and others who are interested in the digital state of Norwegian schools. ICILS-studien (International Computer and Information Literacy Study) undersøker fjortenåringers digitale kompetanse og algoritmiske tenkning. Formålet med studien er å kartlegge hvor godt ungdommer er forberedt på studier, arbeidsliv og hverdagen i en digital verden. Studien gjør det også mulig å sammenligne resultater mellom ulike land og studere hvordan utviklingen av digital kompetanse endres over tid, og gir viktig innsikt i hvordan digitaliseringen påvirker skolen. ICILS har blitt gjennomført hvert femte år siden 2013, og Norge deltok både i 2013 og i 2023. Dette gir oss mulighet til å følge utviklingen av digital kompetanse over tid. I tredje runde deltok også Danmark, Finland og Sverige, noe som gir en unik mulighet til å sammenligne resultater og identifisere likheter og forskjeller mellom disse landene. Denne rapporten presenterer de første funnene for den tredje gjennomføringen av ICILS, sett med norske øyne, og gir en enkel beskrivelse av hovedresultatene. Rapporten er rettet mot et bredt publikum, spesielt skoleledere, lærere og andre som er interessert i den digitale tilstanden i norske skoler.